Ancient hybridization and repetitive element proliferation in the evolutionary history of the monocot genus Amomum (Zingiberaceae) - Hlavatá, Kristýna; Záveská, Eliška; Leong-Škorničková, Jana; Pouch, Milan; Poulsen, Axel Dalberg; Šída, Otakar; Khadka, Bijay; Mandáková, Terezie; Fér, Tomáš (Frontiers in Plant Science, 2024)
Genome size variation is a crucial aspect of plant evolution, influenced by a complex interplay of factors. Repetitive elements, which are fundamental components of genomic architecture, often play a role in genome expansion by selectively amplifying specific repeat motifs. This study focuses on Amomum, a genus in the ginger family (Zingiberaceae), known for its 4.4-fold variation in genome size. Using a robust methodology involving PhyloNet reconstruction, RepeatExplorer clustering, and repeat similarity-based phylogenetic network construction, we investigated the repeatome composition, analyzed repeat dynamics, and identified potential hybridization events within the genus. Our analysis confirmed the presence of four major infrageneric clades (A-D) within Amomum, with clades A-C exclusively comprising diploid species (2n = 48) and clade D encompassing both diploid and tetraploid species (2n = 48 and 96). We observed an increase in the repeat content within the genus, ranging from 84% to 89%, compared to outgroup species with 75% of the repeatome. The SIRE lineage of the Ty1-Copia repeat superfamily was prevalent in most analyzed ingroup genomes. We identified significant difference in repeatome structure between the basal Amomum clades (A, B, C) and the most diverged clade D. Our investigation revealed evidence of ancient hybridization events within Amomum, coinciding with a substantial proliferation of multiple repeat groups. This finding supports the hypothesis that ancient hybridization is a driving force in the genomic evolution of Amomum. Furthermore, we contextualize our findings within the broader context of genome size variations and repeatome dynamics observed across major monocot lineages. This study enhances our understanding of evolutionary processes within monocots by highlighting the crucial roles of repetitive elements in shaping genome size and suggesting the mechanisms that drive these changes.